Systematic Review on COVID-19 Readmission and Risk Factors: Future of Machine Learning in COVID-19 Readmission Studies - Wei Kit Loo; Khairunnisa Hasikin; Anwar Suhaimi; Por Lip Yee; Kareen Teo; Kaijian Xia; Pengjiang Qian; Yizhang Jiang; Yuanpeng Zhang; Samiappan Dhanalakshmi; Khin Wee Lai; Muhammad Mokhzaini Azizan (FRONTIERS, 2024)
Indexed by WOS/SCOPUS/ERA